Mengembangkan Kecerdasan Visual-Spasial Dalam Permainan Puzzle Pada Anak Usia 5-6 Tahun Di Tk Awirrasyidin Sei Mencirim - Masganti Sit; Sagala, Pebrina Hesty; Selian, Suci Nadillah; Nasution, Yelvira Meiniza (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
The low visual-spatial abilities of the students at Awirrasyidin Sei Mencirim Kindergarten led to the conduct of this study. Children struggle to memorize and organize geometric forms, cannot distinguish between right and left, and have trouble distinguishing colors. The purpose of this study is to enhance kids' visual-spatial intelligence by using puzzle games. With 18 kids serving as research subjects, the study was carried out at the Awirrasyidin Sei Mencirim Kindergarten. Observation and documentation are the two methods of data gathering used in this qualitative study. The findings of the study demonstrate that children's visual-spatial intelligence can be enhanced via puzzle games.